1991
DOI: 10.1073/pnas.88.20.9243
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of H-2b-associated resistance to Friend erythroleukemia virus by a class I gene from the H-2d major histocompatibility complex haplotype.

Abstract: Mice homozygous for the H-2d haplotype at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Splenomegaly as a measure of Friend disease. Palpation for splenomegaly is the standard procedure used to monitor the progression of Friend disease (10,15,31) and was used in the following manner. At weekly intervals, each individual animal under general anesthesia was palpated in a blinded fashion and rated on a scale of 1ϩ to 4ϩ according to its spleen size.…”
Section: Methodsmentioning
confidence: 99%
“…Splenomegaly as a measure of Friend disease. Palpation for splenomegaly is the standard procedure used to monitor the progression of Friend disease (10,15,31) and was used in the following manner. At weekly intervals, each individual animal under general anesthesia was palpated in a blinded fashion and rated on a scale of 1ϩ to 4ϩ according to its spleen size.…”
Section: Methodsmentioning
confidence: 99%
“…in cytomegalovirus-induced myocarditis (Lawson et al 1990). and in Friend virus-induced erythroleukemia (Polsky & Lilly 1991). Finally, in an animal model of human MHC-disease association, mice that are transgenic for the HLA-B27 allele are more susceptible to infection with Yersinia than are their nontransgenic Iittermates (Nickerson et al 1990).…”
Section: I) Many Mhc-disease Associations Involve Dominant or Co-domimentioning
confidence: 99%
“…This immunosuppressive effect of H-2 d is similar as for FV because the immunogenicity of the env gene is poor when presented in this context. It has been demonstrated that FV resistance is suppressed by the expression of genes located in the H-2D d region and that D d gene mediates at least in part its effects [30]. Our experiments with MHSV indicate that MHSV has similar properties but that the suppressive effect of the d haplotype probably maps to the left of the D region, that is, either in the K or I-A region.…”
Section: Depletion Of Cd4 ϩ Cells Results In An Increased Susceptibilmentioning
confidence: 56%